Politeness Strategy Used by Teacher in Islamic Boarding School - Hartati, Aisya (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This study deals with Politeness Strategies Used by Teacher in Learning Process at Islamic Boardingschool. This study aims to find out kind of politeness strategies and the way politeness strategies were usedby teacherin the classroom. This research is qualitative study. The data was teacherâs utterances who teach in Islamic Boarding School, the data source was the English teacher. To get the data, the researcher uses tape recorder to record the utterances and transcribe the utterances to find the kind of politeness strategy that is used by the teacher. As the result, from the analysis the researcher found that there are four kinds of politeness strategy used by teacher when the teacher interact to the students. They are greeting, question, command and request. Realize to Brown and Levinsonâs theory, there are politeness strategies that always used by the teacher. They are bald on record and positive politeness strategy that are also the way to use politeness strategy in the classroom. Politeness strategies were used based on the situation and condition in the classroom. The teacher chose the kind of politeness strategies to save the time and try to minimize face threatening acts implicitly and also to communicate to the students for academic purpose and to make the students enjoyable and ease understanding the lesson in learning process.